Histopathological assessment of chronic Corynebacterium pseudotuberculosis infection in the reproductive tract and iliac lymph node of Katjang does - Abdul Latif, Nur Amirah; Abba, Yusuf; Abdullah, Faez Firdaus Jesse; Lim, Eric Teik Chung; Saad, Mohd Zamri; Saharee, Abdul Aziz; Zakaria, Zunita; Haron, Abdul Wahid; Mohd Lila, Mohd Azmi (Springer, 2017)
FAEZ FIRDAUS JESSE BIN ABDULLAH (A03854) / Yusuf Abba / ABDUL AZIZ BIN SAHAREE,ERIC LIM TEIK CHUNG,ABD. WAHID BIN HARON,MOHD ZAMRI BIN SAAD,MOHD AZMI BIN MOHD LILA,ZUNITA BINTI ZAKARIA,NUR AMIRAH BINTI ABDUL LATIF /